2013
DOI: 10.5194/acp-13-8857-2013
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric nitric oxide and ozone at the WAIS Divide deep coring site: a discussion of local sources and transport in West Antarctica

Abstract: The first measurements of atmospheric nitric oxide (NO) along with observations of ozone (O3), hydroperoxides (H2O2 and MHP) and snow nitrate (NO3) on the West Antarctic Ice Sheet (WAIS) were carried out at the WAIS Divide deep ice-coring site between 10 December 2008 and 11 January 2009. Average ±1σ mixing ratios of NO were 19 ± 31 pptv and confirmed prior model estimates for the summer boundary layer above WAIS. Mean ±1σ mixing ratio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 79 publications
2
10
0
Order By: Relevance
“…Data from SP, SY, NM, and HA were retrieved from the WMO World Data Centre for Greenhouse Gases (http://ds.data.jma.go.jp/gmd/wdcgg/ cgi-bin/wdcgg) and updated with data from individual investigators. More details on data from the South Pole can be found in McClure-Begley et al (2014). Details on ozone data from Syowa can also be found at http://ds.data.jma.go.…”
Section: Sites and Methodsmentioning
confidence: 99%
“…Data from SP, SY, NM, and HA were retrieved from the WMO World Data Centre for Greenhouse Gases (http://ds.data.jma.go.jp/gmd/wdcgg/ cgi-bin/wdcgg) and updated with data from individual investigators. More details on data from the South Pole can be found in McClure-Begley et al (2014). Details on ozone data from Syowa can also be found at http://ds.data.jma.go.…”
Section: Sites and Methodsmentioning
confidence: 99%
“…3 and 4). These measurements are made using continuous-flow analysis (CFA) at DRI, following methods adapted from McConnell et al (2002McConnell et al ( , 2007, providing centimeter-scale resolution, which are averaged to the resolution of the isotope records presented here.…”
Section: Comparison Of 17 O To Other Ice Core Recordsmentioning
confidence: 99%
“…This similar level of ozone in air masses having a pure marine origin or having traveled over margin regions of the Antarctic continent is consistent with the study from Frey et al (2005) that showed that photochemical ozone production is not large over inland Antarctic regions located below about 2500 m. A more recent study conducted in the interior of West Antarctica at the WAIS Divide (1766 m a.s.l.) also showed that the local ozone production is too small to explain the observed ozone variability and that events with increased surface ozone in summer are systematically linked to rapid (< 3 days) transport off the East Antarctic plateau via katabatic outflow (Masclin et al, 2013). The preceding sequence of changing air mass origin (ocean, Antarctic plateau above 3000 m a.s.l., and coastal regions of the Antarctic continent) was encountered again from 14 to 27 December, with ozone levels of 16.7 ppbv between 14 December in the evening and 17 December in the morning (marine origin, see the grey right arrow in Fig.…”
Section: Ddumentioning
confidence: 99%
“…The oxidative properties of the atmosphere of inland Antarctica were mainly investigated at the South Pole through the ISCAT (Investigation of Sulfur Chemistry in Antarctica) projects in 1998 (Davis et al, 2001) and 2000 , followed by the Antarctic Tropospheric Chemistry Investigation (ANTCI, project in 2003. Studies of oxidants in the atmospheric boundary layer including ozone were also carried out in summer above the West Antarctic Ice Sheet (WAIS) as part of scientific overland traverses (Frey et al, 2005) and deep ice core drilling at WAIS Divide (Masclin et al, 2013).…”
mentioning
confidence: 99%